Bilateral Obstructive Uropathy Secondary to Giant Periureteral Diverticulum - Alberto Hernando Arteche; Luis Alberto San Jose Manso; Carlos Olivier Gomez; Angel Nellyt Silmi Moyano (Case Reports in Urology)
Bladder diverticula are herniations of the mucosa through the fibers of the bladder muscle connected by necks of variable amplitude. They are often asymptomatic, although they may lead to complications that require a surgical therapeutic approach. We report the case of a patient with bilateral obstructive uropathy secondary to a giant periureteral diverticulum that was treated by diverticulectomy and reimplantation of the left ureter in the bladder.